Phase II, Double-Blinded, Randomized, Placebo-Controlled Clinical Trial Investigating the Efficacy of Mebendazole in the Management of Symptomatic COVID-19 Patients - Mohamed El-Tanani; Khaled Abdul-Aziz Ahmed; Ashok K. Shakya; Wesam G. Ammari; Abdel-E (MDPI AG, 2023)
The outbreak of the COVID-19 pandemic has spread throughout the world, affecting almost all nations and territories. The current double-blind, randomized, placebo-controlled, phase II clinical trial sought to evaluate the clinical efficacy and safety of mebendazole as an adjuvant therapy for outpatients with COVID-19. The patients were recruited and divided into two groups: a Mebendazole-treated group and placebo group. The mebendazole and placebo groups were matched for age, sex, and complete blood count (CBC) with differential and liver and kidney function tests at baseline. On the third day, the C-reactive protein (CRP) levels were lower (2.03 ± 1.45 vs. 5.45 ± 3.95, p < 0.001) and the cycle threshold (CT) levels were higher (27.21 ± 3.81 vs. 24.40 ± 3.09, p = 0.046) significantly in the mebendazole group than in the placebo group on the third day. Furthermore, CRP decreased and CT dramatically increased on day three compared to the baseline day in the mebendazole group (p < 0.001 and p = 0.008, respectively). There was a significant inverse correlation between lymphocytes and CT levels in the mebendazole group (r = −0.491, p = 0.039) but not in the placebo group (r = 0.051, p = 0.888). Mebendazole therapy increased innate immunity and returned inflammation to normal levels in COVID-19 outpatients faster than it did in the placebo group in this clinical trial. Our findings add to the growing body of research on the clinical and microbiological benefits of repurposing antiparasitic therapy, specifically mebendazole, for SARS-CoV-2 infection and other viral infections.